Shiny objects : why we spend money we don't have in search of happiness we can't buy - Roberts, James A. (James Andrew) (HarperOne, 2011)
Roberts, professor of marketing at Baylor University, studies why Americans believe and behave as if possessions will induce, increase, and enhance happiness. His inquiry provides ample psychological and historical insights as well as self-assessment quizzes on how much we spend and how vulnerable we are to status anxiety.